Low‐intensity environmental education can enhance perceptions of culturally taboo wildlife. Issue 7 (19th July 2021) - Williams, Samual T.; Williams, Kathryn S.; Constant, Natasha; Swanepoel, Lourens; Taylor, Peter J.; Belmain, Steven R.; Evans, Steven W.
Abstract: Traditional cultural beliefs influence perceptions of animals and can result in persecution of wildlife. In Africa, stigmas against species associated with witchcraft can act as a barrier to the uptake of sustainable practices such as reducing crop damage through reliance on indigenous predators rather than pesticides to control rodent agricultural pests. One way of enhancing perceptions of wildlife to increase participation in ecologically based rodent management schemes is through environmental education. Low‐intensity programs can produce positive attitudinal shifts, but their impact has not been assessed for species strongly associated with witchcraft. We tested whether a presentation on the natural history of owls in the Limpopo Province of South Africa could improve perceptions of these species and increase willingness to participate in the installation of owl boxes to increase owl populations and reduce rodent populations and crop damage. We used a pre‐ and post‐survey to assess the perceptions of owls of 340 learners aged between 12 and 18 in four schools before and after listening to the presentation. Respondents that watched the presentation had more positive perceptions of owls than those that had not watched the presentation and were more willing to put up owl boxes near their home. Despite this shift, negative perceptions of owls still dominated responses due to cultural associations with the occult. These findings indicate that even low‐intensity programs can be effective at enhancing perceptions of taboo wildlife. We suggest that environmental education programs featuring culturally taboo species should adopt a culturally sensitive approach to focus on the benefits these species provide.